Do New Technologies of Information and Communication Improve the Processes of Teaching and Learning Mathematics? - Parra Vargas, Rita Helena (Rastros Rostros, 2012)
The main purpose of this paper is to account for the influence of new technologies of information and communication in the processes of teaching and learning mathematics. Disclosed are some researches that show positive results in the educational process and that served as a framework for a research project focused on the use of a website and the Cabri software for learning the concept of quadrilaterals in the seventh grade of the Instituto La Cumbre of the Municipality of Floridablanca. The ongoing research that gave rise to this paper is called “Do New Technologies of Information and Communication Improve the Processes of Teaching and Learning Mathematics?” which was developed in 2011 and 2012 at the Universidad del Tolima. This was carried out with the purpose of improving teaching and learning processes incorporating teaching strategies that include new information and communication technologies to encourage the study of geometry, and allow students to get better performance.
Keywords: learning; didactic; teaching; mathematics; new technologies